Biodiversity conservation in Costa Rica : learning the lessons in a seasonal dry forest - Frankie, G. W.; Mata, Alfonso; Vinson, S. Bradleigh, 1938- (University of California Press, 2004)
Based on more than 30 years of study, this text offers a comprehensive look at the ecology, biodiversity, and conservation status of the endangered and fragile tropical dry forest of northwest Costa Rica.